ANALISIS KESULITAN BELAJAR MATEMATIKA MATERI PEMBAGIAN KELAS II A SD NEGERI 2 KAMPUNG BARU - Solihah, Annida; Mashari, Ali; Soraya, Rahayu (AHSANTA JURNAL PENDIDIKAN, 2024)
This research aims to find out the causes of difficulties in learning mathematics in division material experienced by class II A students and the factors that influence difficulties in learning mathematics in division material in class II A students at SD Negeri 2 Kampung Baru Bandar Lampung. The research method used in this research is descriptive qualitative. The research subjects in this study were 21 students in class II A, teachers and parents. Data collection techniques in this research were carried out using observation, interviews and documentation. The data analysis technique goes through three stages, namely, data reduction, data display, and conclusion drawing/verification. Based on the research results, it can be concluded that the learning difficulties experienced by students are caused by difficulties in understanding the concept of division, weak students' numeracy skills, students have difficulty understanding story problems, students have difficulty doing division in repeated subtraction material. Meanwhile, the factors that influence the difficulty of learning mathematics division material consist of two factors, namely internal factors, internal factors including psychological factors (students' low interest in learning, difficulty concentrating, not being ready to receive lessons, and lack of response when studying) and physical factors such as students who have weakness in health. External factors include lack of use of learning media, poor relationships between students who have learning difficulties with other students in the class, lack of attention from parents and less harmonious family conditions